Australian Cancer Physicians and the Pharmaceutical Industry: A Survey of Attitudes and Interactions. Issue 7 (22nd July 2022) - Pokorny, Adrian M.J.; Moynihan, Ray; Fox, Peter; Karikios, Deme J.; Bero, Lisa A.; Mintzes, Barbara J.
Abstract : PURPOSE: Interactions between cancer physicians and the pharmaceutical industry may create conflicts of interest that can adversely affect patient care. We aimed to survey cancer physicians regarding their attitudes toward and interactions with industry. METHODS: We surveyed Australian cancer physicians between December 2020 and February 2021, questioning how often they interacted with industry and their attitudes toward this. We also assessed factors associated with accepting payments from industry and the amount received, and opinions on policies and industry influence. We used logistic and linear regression to examine links between attitudes and behaviors. RESULTS: There were 116 responses (94 complete). Almost half (n = 53 of 115, 46.1%) felt that there was a positive relationship between cancer physicians and industry. Most (n = 79 of 104, 76.0%) interacted with industry at least once a month, and 67.7% (n = 63 of 93) had received nonresearch payments from industry previously, with a median value of 2, 000 Australian dollars over 1 year. Most respondents believed that interactions could influence prescribing while simultaneously denying influence on their own prescribing (n = 66 of 94, 70.2%). Those who judged general sales representative interactions (odds ratio [OR] 9.37 [95% CI, 1.05 to 83.41], P = .045) or clinician sponsorship (OR 3.22 [95% CI, 1.01 to 10.30], P = .049) to be more acceptable also met with sales representatives more frequently. Physicians were more likely to accept industry payments when they deemed sponsorship of clinicians for conferences (OR 10.55 [95% CI, 2.33 to 47.89], P = .002) or honoraria for advisory board membership more acceptable (OR 3.91 [95% CI, 1.04 to 14.74], P = .04) or when they had higher belief in industry influence over own prescribing (OR 25.51 [95% CI, 2.70 to 241.45], P = .005). CONCLUSION: Australian cancer physicians interact with industry frequently, and those who feel positive about these interactions are likely to do so more often. More research is needed to understand the motivations behind these interactions.